Law’s Evolving Emergent Phenomena: From Rules of Social Intercourse to Rule of Law Society - Brian Tamanaha (Washington University Law Review, 2018)
Law involves institutions rooted in the history of a society that evolve in relation to surrounding social, psychological, cultural, economic, political, technological, and ecological influences. Law must be understood naturalistically, historically, and holistically. In my usage, naturalism views humans as social animals with natural traits and requirements, historicism presents law as historical manifestations that change over time, and holism sees law within social surroundings. These insights inform my perspective in A Realistic Theory of Law. While these propositions might seem obvious, few works in contemporary jurisprudence build around them. In this essay, I draw on the notion of emergence to further elaborate the implications of naturalism, historicism, and holism for legal theory. Emergent phenomena arise in connection with objects or agents whose interactions produce qualitatively new features not found in its constituent parts. Two senses of emergence are contained in this idea: the emergent phenomenon is greater than the sum of its parts, and its emergence is a historical occurrence. Theories of emergence were originally articulated in a late nineteenth and early twentieth century reaction against scientific reductionism. Originating in biological theories of evolution, emergence was extended to explain a range of phenomena, including the transition in levels from physics, to chemistry, to biology, to the emergence of consciousness from material brains, to the emergence of social structures from the actions of individuals. Emergence is enjoying renewed attention as a component of complexity theory. However, I will use the notion of emergence to illuminate aspects of law without grounding the analysis in complexity theory. First, I introduce emergence. Then I describe five emergent aspects of law: fundamental rules of social intercourse; legal systems as organized coercion; specialized legal knowledge; a relatively fixed legal fabric; and a rule of law society. The first three emergent phenomena in combination constitute fundamental features of modern legal systems. The two remaining emergent phenomena relate to law in contemporary society. In the course of describing these aspects of law, I address implications for various important issues in legal theory exposed by seeing them as emergent phenomena.
Keywords: A Realistic Theory of Law; Jurisprudence; Legal systems; Legal fabric; Rule of law; Emergent legal phenomena; Legal theory